An Overview of Lifestyle in Communities During The Second Wave of Covid-19 Pandemic - Eppy Setiyowati; Umi Hanik; Nunik Purwanti (Universitas Nahdlatul Ulama Surabaya, 2021)
Coronavirus 2019 (COVID-19) is a virus causing high mortality rates in various countries. So, the communities make preventive efforts with healthy lifestyle behaviors. The research aims to study lifestyle behaviors and community health conditions during the Covid 19 pandemic. This paper was a quantitative research design with a cross- sectional approach. In addition, the population was 170 respondents domiciled in Surabaya. Sampling techniques used simple random sampling. Data collection through the dissemination of questionnaires in google form circulated through WhatsApp group. Furthermore, the data were analyzed with a Linear Regression Test with  = 0.005. The analysis results gained public knowledge about the COVID-19 pandemic in the Low category (13.94%). In addition, in public behavior variable showed that the community did not comply with health protocols during the COVID-19 pandemic (59.18%). Most respondents were in the category of low-risk cases. Linear statistic regression test results showed lifestyle related to knowledge, healthy behavior, obedient protocol Health and health condition in individuals (= 0007). Public Health Condition is an indicator of the successful assessment of the disconnection of the covid 19 spread chain. Future research should analyze awareness, compliance, and the willingness of the community to carry out health protocols.